Intratumoral oncolytic virus OH2 injection in patients with locally advanced or metastatic sarcoma: a phase 1/2 trial - Lu Zhang; Shu Li; Jing Huang; Yan Wu; Liang Han; Tian Gao; Qingxia Fan; Suxia Luo; Binlei Liu; Lixin Zhou; Xinyu Wang; Ling Jia; et al. (Journal for ImmunoTherapy of Cancer)
Background Intratumoral oncolytic herpes simplex virus 2-GM CSF (OH2) injection has shown safety and antitumor efficacy in patients with solid tumors. Here, we examined the safety and efficacy of OH2 as a single agent or in combination with HX008, an NMPA-approved PD-1 inhibitor, in locally advanced or metastatic sarcoma patients.Methods This multicenter, phase 1/2 trial enrolled patients with injectable sarcoma lesions, who had failed at least 1 or more lines of standard treatment. Patients were treated with OH2 at three dose levels (106, 107 and 108 CCID50/mL) as single agent or in combination with a fixed dose of HX008. The primary endpoints were safety and tolerability in phase 1 and objective response rate determined by RECIST (V.1.1) criteria and immune-RECIST in phase 2.Results Between October 20, 2020 and December 30, 2023, 26 patients were enrolled. Seven patients were treated with single-agent OH2 and 19 with HX008 and OH2 combination. No dose-limiting toxicities were observed during the dose escalation. We documented four partial or complete responses in injected lesions, and one partial response in non-injected lesions, which were all from the combination group. Hence, the overall response rate was 0% and 16.7% in the single agent and combination groups, respectively. The duration of response was 3.9–6.5 months. The most frequent treatment-related adverse events (TRAEs) were fever (n=9). Grade 3 or 4 TRAEs were reported in four patients (15.4%). A clear increase in CD8+cell density in the tumor microenvironment was observed in the patients’ post-treatment specimens compared with baseline.Conclusions Intratumoral injection of oncolytic virus OH2 is well tolerable in patients with sarcoma. Further investigation of OH2 with HX008 in select sarcoma subtypes is warranted.